Neurotoxic effects of thimerosal at vaccines doses on the encephalon and development in 7 day-old hamsters - Remuzgo, Fany (2007)
Objectives: To determine if thimerosal administration in amounts equivalent to vaccines content produces neurotoxic effects on the encephalon in postnatal hamsters and on experimentation animals' development. Design: Experimental, prospective, bietapic study. Setting: San Fernando Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Biologic material: Seven-day old hamsters. Material: We divided 45 postnatal hamsters in three groups: group A (n = 15), group B (n = 15) and group C (n = 15). We administered three intramuscular equivalent doses of sucrose and thimerosal in 20 μL of physiological serum respectively to groups B and C on birth-days 7 (0,227 μg), 9 (0,216 μg) and 11 (0,220 μg). Group A received only 20 μL of saline solution. Main outcome measures: Body weight, encephalon weight, hamster's stature and encephalon histopathological alterations. Results: Anova and student t tests showed statistical significance in favor of low body weight, low encephalon weight and smaller stature in group C with respect to groups A and B hamsters (p<0,000). χ2 statistical significance in relation to the presence of histopathological alterations in group C was also obtained (p<0,000). We observed greater relative risk of encephalic alterations in group C. Conclusions: The administration of thimerosal in doses equivalent to vaccines content was associated with low corporal weight, low encephalon weight and smaller stature in postnatal hamsters. Neurotoxic effects were also produced at encephalic level, at hippocampus (regions CA1, CA3, DG), cerebral cortex and cerebellum (Purkinje cells and granuloses cells) with decrease in neuronal density, neuronal necrosis, axonal dismyelinization and gliosis. In addition, risk increase in developing any of these alterations was high in the animal group receiving thimerosal.